Increased glutaminyl cyclase activity in brains of Alzheimer's disease individuals. Issue 6 (20th July 2020) - Gunn, Adam P.; Wong, Bruce X.; McLean, Catriona; Fowler, Chris; Barnard, Peter J.; Duce, James A.; Roberts, Blaine R.; ,
Abstract: Glutaminyl cyclases (QC) catalyze the formation of neurotoxic pGlu‐modified amyloid‐β peptides found in the brains of people with Alzheimer's disease (AD). Reports of several‐fold increases in soluble QC (sQC) expression in the brain and peripheral circulation of AD individuals has prompted the development of QC inhibitors as potential AD therapeutics. There is, however, a lack of standardized quantitative data on QC expression in human tissues, precluding inter‐laboratory comparison and validation. We tested the hypothesis that QC is elevated in AD tissues by quantifying levels of sQC protein and activity in post‐mortem brain tissues from AD and age‐matched control individuals. We found a modest but statistically significant increase in sQC protein, which paralleled a similar increase in enzyme activity. In plasma samples sourced from the Australian Imaging, Biomarker and Lifestyle study we determined that QC activity was not different between the AD and control group, though a modest increase was observed in female AD individuals compared to controls. Plasma QC activity was further correlated with levels of circulating monocytes in AD individuals. These data provide quantitative evidence that alterations in QC expression are associated with AD pathology. Abstract : Neurotoxic pyroglutamate‐modified amyloid‐β (pGlu‐Aβ) peptides are abundant in Alzheimer's disease (AD) brains – their formation catalyzed by glutaminyl cyclases (QC). Previous reports describing several‐fold increases of QC expression in AD tissues are evidenced primarily by relative quantification, without standardization. We demonstrate here a quantitative increase in QC protein and activity in the AD frontal cortex, further demonstrating that different anti‐QC antibodies yield different results in comparisons of control and AD brain tissues. We additionally investigated the association of plasma QC activity with levels of dementia, thyroid hormones and circulating monocytes.